2020
DOI: 10.1002/app.49325
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior, in vitro drug release, and antibacterial activity of thermoresponsive poloxamer–polyvinyl alcohol hydrogel‐loaded mupirocin nanoparticles

Abstract: This research was designed to develop thermoresponsive poloxamer (P407)–polyvinyl alcohol (PVA) hydrogels to deliver mupirocin nanoparticles for wound healing. The mupirocin nanoparticles containing drug and gelatin or poly (acrylic acid) were prepared by spray drying. The hydrogel phases were evaluated by small‐angle X‐ray scattering. An in vitro drug release study was performed and the antibacterial activity of mupirocin nanoparticles‐loaded hydrogel (MLH) was evaluated. Fourier transform infrared and proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This approach can be utilized to provide the sustained release of sparingly soluble drugs. A thermoresponsive poloxamer (P407)-polyvinyl alcohol gel was developed to deliver mupirocin nanoparticles for wound healing [ 27 ]. Silver sulfadiazine/nanosuspensions (AgSD/NS) were prepared and loaded into poloxamer 407-based TGs as carriers of AgSD/NS to obtain AgSD/NS-loaded TGs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can be utilized to provide the sustained release of sparingly soluble drugs. A thermoresponsive poloxamer (P407)-polyvinyl alcohol gel was developed to deliver mupirocin nanoparticles for wound healing [ 27 ]. Silver sulfadiazine/nanosuspensions (AgSD/NS) were prepared and loaded into poloxamer 407-based TGs as carriers of AgSD/NS to obtain AgSD/NS-loaded TGs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the establishment of an appropriate drug release model, through the fitting of the experimental data, was an effective means to simulate and predict the release behavior of MXD-TG. It was reported that the hydrogel-loaded mupirocin nanoparticles fitted the first-order kinetics, which showed that the drug release was controlled mainly by diffusion [ 27 ]. Differently, the gemcitabine release of high-molecular-weight hyaluronic-acid-added gel was diffusion-erosion controlled [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was interpreted as there is no chemical bond interaction between the molecules of the mupirocin and the molecules of the carriers and that the mupirocin is surrounded by the molecules of the carrier. 219 Gu ¨ven and Yenilmez produced Kollidon SR NPs containing antiallergic olopatadine hydrochloride with a nano spray dryer. 176 NMR analysis was performed on pure olopatadine hydrochloride, Kollidon SR physical mixture, and drugloaded NPs.…”
Section: Nmr Analysismentioning
confidence: 99%
“…In contrast to MUP, MLH exhibited a progressive controlled drug release ointment due to the cubic phase behavior of thermosensitive polymer and PVA hydrogel. The MLH exhibited reduced MIC and minimum bactericidal concentrations against S. aureus, S. epidermidis, Pseudomonas aeruginosa, and E. coli compared to the MUP ointment [57]. Recently, the same group studied the biocompatibility and safety of MLH for wound healing in the rat model.…”
Section: Nanoparticles/naocapsulesmentioning
confidence: 99%